Emotional state detection based on common spatial patterns of EEG - DURU, ADİL DENİZ (SPRINGER LONDON LTD, 2020)
The application of EEG-based emotional states is one of the most vital phases in the context of neural response decoding. Emotional response mostly appears in the presence of visual, auditory, tactile, and gustatory arousals. In our work, we use visual stimuli to evaluate the emotional feedback. One of the best performing methods in emotion estimation applications is the common spatial patterns (CSP). We implement CSP method in addition to the conventional Welch power spectral density-based analysis. Experimental results and topographies on the collected EEG data show that the CSP spatial filtering method implies the relationship between EEG bands, EEG channels, neural efficiency and emotional stimuli types.
Keywords: EEG; Power spectral density; Common spatial pattern; Neural efficiency; ANOVA; RECOGNITION; EXTRACTION; BRAIN